Safety, Pharmacokinetics, and Pharmacodynamics in Healthy Volunteers Treated With GDC‐0853, a Selective Reversible Bruton's Tyrosine Kinase Inhibitor. Issue 6 (23rd March 2018) - Herman, Ann E.; Chinn, Leslie W.; Kotwal, Shweta G.; Murray, Elaine R.; Zhao, Rui; Florero, Marilyn; Lin, Alyse; Moein, Anita; Wang, Rena; Bremer, Meire; Kokubu, Serika; Serone, Adrian P.; et al.
Abstract : GDC‐0853 is a small molecule inhibitor of Bruton's tyrosine kinase (BTK) that is highly selective and noncovalent, leading to reversible binding. In double‐blind, randomized, and placebo‐controlled phase I healthy volunteer studies, GDC‐0853 was well tolerated, with no dose‐limiting adverse events (AEs) or serious AEs. The maximum tolerated dose was not reached during dose escalation (≤600 mg, single ascending dose (SAD) study; ≤250 mg twice daily (b.i.d.) and ≤500 mg once daily, 14‐day multiple ascending dose (MAD) study). Plasma concentrations peaked 1–3 hours after oral administration and declined thereafter, with a steady‐state half‐life ranging from 4.2–9.9 hours. Independent assays demonstrated dose‐dependent BTK target engagement. Based on pharmacokinetic/pharmacodynamic (PK/PD) simulations, a once‐daily dosing regimen (e.g., 100 mg, q.d.) is expected to maintain a high level of BTK inhibition over the dosing interval. Taken together, the safety and PK/PD data support GDC‐0853 evaluation in rheumatoid arthritis, lupus, and other autoimmune or inflammatory indications.